What matters to the public when they call the police? Insights from a call centre. (18th May 2016) - Stafford, Andrew B.
Abstract : Contact with the police impacts upon public judgements of the police. The experiences of those who contact the public police by telephone concerning non-emergency issues have received little attention in the existing literature. This article presents findings from a qualitative examination of a police Constabulary's non-emergency call-handling processes, exploring some of the factors which shaped the contact experienced through this channel. Interviews were conducted with 70 members of the public who contacted the Constabulary through its call centre, with the police call-handlers who answered some of these calls, and with call centre supervisors and senior managers. Police call-handlers were positive about their jobs, despite acknowledging the somewhat repetitive nature of the work, as they believed they were helping the public by providing a valuable, worthwhile service. Callers were primarily concerned with how they were treated and noted that the most memorable and helpful components of their calls to the police were the ways in which call-handlers conveyed empathy, understanding, interest, sensitivity and politeness. Having a call answered in under 40 seconds, one of the quantitative performance targets used to measure performance in the police call centre, appeared to be less important to callers. The article concludes by arguing that quantitative targets are ill-suited to measuring and supporting the kind of emotional labour that call-handlers undertake and the emotional engagement that callers value. Providing high-quality service should be the priority for police call centres, as this is likely to generate positive judgements of the police.